Pemanfaatan Aplikasi MySQL untuk Membantu Siswa SMK Swasta Nur Azizi dalam Pengolahan Data - Siregar, Yunita Sari; Oktaviana Sembiring, Boni; Rahayu, Eka; Hasdiana, Hasdiana; Franchitika, Rizky (Jurnal Pengabdian Masyarakat, 2024)
The rapid development of technology has influenced various aspects of education, including data management in schools. One of the key aspects of vocational education is efficient data processing to support administrative and academic activities. This community service program was conducted to provide students of SMK Swasta Nur Azizi with knowledge and skills in utilizing MySQL as a database management system for data processing. MySQL was chosen for its capability to efficiently manage and process data, making it highly relevant to industry needs. This program employed a qualitative approach with a case study method, focusing on the implementation of MySQL in student data processing. Data were collected through interviews, observations, and documentation to analyze the effectiveness of MySQL in school operations. The activities included socialization sessions covering theoretical explanations of MySQL fundamentals, software installation, and hands-on practice in database creation and SQL queries. The results of this program indicate that students were able to understand the basic concepts of MySQL, create databases and tables, and process data using fundamental SQL commands such as SELECT, INSERT, UPDATE, and DELETE. Thus, this initiative is expected to enhance students' data processing skills, enabling them to apply these competencies in various fields and strengthen their qualifications in the job market.